ANTENATALCARE ANALYSIS BY MIDWIFE IN COMMUNITY HEALTH CENTERS PENGARENGAN SAMPANG BASED ON HEALTH BELIEF MODEL THEORY - Chandra Kartika Dewi (JURNAL KESEHATAN INDRA HUSADA, 2020)
Background : According to the results Riskesdas 2013, the healthcare of mother and children is one of the health issues that concern the world. Purpose : The object of this research is to analyze the influence of behavioral factors on the performance of midwife with health belief models theory approach in Pangarengan community health center. Method : This was a observational research conducted cross-sectional in August-October 2019. The technique to collect data were questionaire and check list. The data utilized were both primary and secondary data. The population in this study were all midwives working in community health centers Pengarengan totaling twenty people. The frequency distribution was used to analyze the data. Result: Based on linear regression analisys obtained perceived severity, perceived susceptibility and cues to actions had a positive influence on the behavior of the midwife. While the perceived barriers, perceived benefits and self efficacy had the opposite effect. Conclusion: health belief model of theory have an impact on behavior improvement Pengarengan antenatal care at the health center. Suggestion: Further research needs to be done about the behavior of the performance in order to improve the quality of antenatal care.